FACTORS AFFECTING IPO UNDERPRICING - Darryl , Darryl; Yusbardini , Yusbardini (International Journal of Application on Economics and Business, 2023)
One of the means for companies to carry out an initial offering of shares or what is commonly known as an Initial Public Offering (IPO) in the primary market. In conducting an initial share offering there is an underpricing phenomenon. Underpricing is a phenomenon where the initial offering price of shares is lower than the closing price of shares on the first day on the secondary market. The aim of this research is to determine the factors that influence the level of underpricing. The independent variables studied are company size, underwriter reputation, return on assets (ROA), and earnings per share (EPS). The population in this research is all companies that conducted an IPO on the Indonesia Stock Exchange in 2015-2020. The sampling technique uses a purposive sampling technique, namely selecting samples using predetermined criteria, so that the sample obtained is 50 companies. The analysis method in this research uses multiple linear regression. The research results show that company size has a significant effect on underpricing, underwriter reputation, and return on assets (ROA), and underpricing.